Synthesis, Characterization, Antibacterial, Antioxidant Studies of New 2-(5-(2-((1E,2E)-3- (2-methoxyphenyl)allylidene)hydrazinyl)-1,3,4- oxadiazol-2-yl)Phenol with the Some Transition Metalions - Awaid Namah, Fayez; A. Flifel , Ibrahim; A. Ali , Saher (International Journal of Psychosocial Rehabilitation, 2020)
A new ligand, 2-(5-(2-((1E,2E) -3-(2-methoxyphenyl)allylidene)hydrazinyl) -1,3,4-oxadiazol-2-yl)phenol and its complexes with Cr(ІІІ), Co(ІІ), Ni(ІІ), and Cu(ІІ) ions were synthesized. The new ligand and its complexes have been characterized on the basis of their spectra of H1NMR, mass, Fourier transform infrared (FTIR), as well as magnetic susceptibility, elemental analysis (CHN), and conductance measurements. The program of HyperChem 8 has been used for theoretical accounts using the PM3 method to study the electrostatic potential that provided good information about the complexity site. Of the result obtained, we can suggest octahedral geometries for Cr(ІІІ), tetrahedral geometry for Co(ІІІ), and square planar geometry for Ni(ІІ) and Cu(ІІ). The antioxidant activity of the ligand was evaluated by DPPH scavenging, and the ligand showed high antioxidant activity. The ligand and its complex gave good activity antibacterial.